Reading weather : the field guide to forecasting the weather - Woodmencey, Jim, 1957- (Falcon guide., 2012)
"Reading Weather provides a quick and simple way to understand how the atmosphere works, how to interpret and use weather forecasts before venturing outdoors, and also how to make your own forecast in the field by observing the changes in the weather. This fully updated and revised reference will arm you with the meteorological knowledge necessary to make good decisions on whether to proceed or retreat in the face of a storm. Also included are helpful definitions, tables, and simplified graphics of common weather features"--P. [4] of cover.